Natural formation of chloro- and bromoacetone in Salt Lakes of Western Australia - Sattler, Tobias; Sörgel, Matthias; Wittmer, Julian; Bourtsoukidis, Efstratios; Krause, Torsten; Atlas, Elliot; Benk, Simon; Bleicher, Sergej; Kamilli, Katharina; Ofner, Johannes; Kopetzky, Raimo; Held, Andreas; et al. (Atmosphere, 2019)
Western Australia is a semi-/arid region known for saline lakes with a wide range of geochemical parameters (pH 2.5–7.1, Cl− 10–200 g L−1). This study reports on the haloacetones chloro- and bromoacetone in air over 6 salt lake shorelines. Significant emissions of chloroacetone (up to 0.2 µmol m−2 h−1) and bromoacetone (up to 1. 5 µmol m−2 h−1) were detected, and a photochemical box model was employed to evaluate the contribution of their atmospheric formation from the olefinic hydrocarbons propene and methacrolein in the gas phase. The measured concentrations could not explain the photochemical halogenation reaction, indicating a strong hitherto unknown source of haloacetones. Aqueous-phase reactions of haloacetones, investigated in the laboratory using humic acid in concentrated salt solutions, were identified as alternative formation pathway by liquid-phase reactions, acid catalyzed enolization of ketones, and subsequent halogenation. In order to verify this mechanism, we made measurements of the Henry’s law constants, rate constants for hydrolysis and nucleophilic exchange with chloride, UV-spectra and quantum yields for the photolysis of bromoacetone and 1,1-dibromoacetone in the aqueous phase. We suggest that heterogeneous processes induced by humic substances in the quasi-liquid layer of the salt crust, particle surfaces and the lake water are the predominating pathways for the formation of the observed haloacetones.
Gesehen am